Mycobacterial Aminoglycoside Acetyltransferases: A Little of Drug Resistance, and a Lot of Other Roles - Sanz-García, Fernando; Anoz-Carbonell, Ernesto; Pérez-Herrán, Esther; Martín, Carlos; Lucía, Ainhoa; Rodrigues, Liliana; Aínsa, José A. (Frontiers in Microbiology, 2019)
Aminoglycoside acetyltransferases are important determinants of resistance to aminoglycoside antibiotics in most bacterial genera. In mycobacteria, however, aminoglycoside acetyltransferases contribute only partially to aminoglycoside susceptibility since they are related with low level resistance to these antibiotics (while high level aminoglycoside resistance is due to mutations in the ribosome). Instead, aminoglycoside acetyltransferases contribute to other bacterial functions, and this can explain its widespread presence along species of genus Mycobacterium. This review is focused on two mycobacterial aminoglycoside acetyltransferase enzymes. First, the aminoglycoside 2′-N-acetyltransferase [AAC(2′)], which was identified as a determinant of weak aminoglycoside resistance in M. fortuitum, and later found to be widespread in most mycobacterial species; AAC(2′) enzymes have been associated with resistance to cell wall degradative enzymes, and bactericidal mode of action of aminoglycosides. Second, the Eis aminoglycoside acetyltransferase, which was identified originally as a virulence determinant in M. tuberculosis (enhanced intracellular survival); Eis protein in fact controls production of pro-inflammatory cytokines and other pathways. The relation of Eis with aminoglycoside susceptibility was found after the years, and reaches clinical significance only in M. tuberculosis isolates resistant to the second-line drug kanamycin. Given the role of AAC(2′) and Eis proteins in mycobacterial biology, inhibitory molecules have been identified, more abundantly in case of Eis. In conclusion, AAC(2′) and Eis have evolved from a marginal role as potential drug resistance mechanisms into a promising future as drug targets.